Towards efficient information sharing in network markets - Bertin Martens; Geoffrey Parker; Georgios Petropoulos; Marshall Van Alstyne (Bruegel, 2021)
Digital platforms facilitate interactions between consumers and merchants that allow collection of profiling information, which drives innovation and welfare. Private incentives, however, lead to information asymmetries resulting in market failures both on-platform, among merchants, and off-platform, among competing platforms. This paper develops two product-differentiation models to study private and social incentives to share information within and between platforms. We show that there is scope for ex-ante regulation of mandatory data sharing that improves social welfare better than competing interventions, such as barring entry, break-up, forced divestiture or limiting recommendation steering. These alternate proposals do not make efficient use of information. We argue that the location of data access matters and develop a regulatory framework that introduces a new data right for platform users, the in-situ data right, which is associated with positive welfare gains. By construction, this right enables effective sharing of information together with its context, without reducing the value created by network effects. It also enables regulatory oversight but limits data privacy leakages. We discuss crucial elements of its implementation in order to achieve innovation-friendly and competitive digital markets.
Keywords: D47; D82; K21; L21; L22; L40; L41; L43; L51; L86; 330; Information sharing; data rights; digital platforms; market failure; in-situ; algorithms; data portability